Penggunaan "USEMAP" Untuk Analisis Perubahan Bentuk Penggunaan Lahan = The Use of USEMAP for Landuse Change Analysis - Prabowo Adi Nugroho (Majalah Geografi Indonesia, 1988)
Current information of landuse and landuse type change within a certain period of time is chiefly needed in a landuse planning. The information of landuse type change is obtainable through overlapping landuse maps of one period. However, the common problem is inavailability of the latest maps, especially those of the areas where the landuse change is rapid. The aerial photographs and remote sensing image can be used to solve the problem. Nevertheless, another problem which is not less important is the need for rapid analysis with high accuracy. For this purpose, computer well-known as Geographical Information System (GIS) is used . One of the GIS components is software, while USEMAP is one of the various hinds of software. The use of USEMAP for landuse change analysis is very effective, especially for the quantitative one. However, USEMAP has some shortcoming, namely this can only be used to analyze seven landuse types.